2023
DOI: 10.3389/fimmu.2023.1233994
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of rheumatoid arthritis through traditional Chinese medicine: role of the gut microbiota

Yujiao Liang,
Mengyao Liu,
Yingxue Cheng
et al.

Abstract: Recently, despite the increasing availability of treatments for Rheumatoid arthritis (RA), the incidence of RA and associated disability-adjusted life years have been on the rise globally in the late decades. At present, accumulating evidence has been advanced that RA is related to the gut microbiota, therefore, the therapeutic approaches for RA by regulating the gut microbiota are anticipated to become a new means of treatment. Traditional Chinese medicine (TCM) can regulate immunity, reduce inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The findings revealed distinct variations in analgesic effects among the three alkaloids. Specifically, at a dosage of 2 mg/kg, the mice exhibited pain inhibition rates of 81.6%, 58.5%, and 51.2% for compounds 15 , 38 , and 39 , respectively ( Liang et al, 2023 ). Furthermore, the LD 50 values for the three alkaloids were determined as 4.06 mg/kg, 2.81 mg/kg, and 12.00 mg/kg, respectively.…”
Section: Pharmacological Activities Of Acmentioning
confidence: 99%
“…The findings revealed distinct variations in analgesic effects among the three alkaloids. Specifically, at a dosage of 2 mg/kg, the mice exhibited pain inhibition rates of 81.6%, 58.5%, and 51.2% for compounds 15 , 38 , and 39 , respectively ( Liang et al, 2023 ). Furthermore, the LD 50 values for the three alkaloids were determined as 4.06 mg/kg, 2.81 mg/kg, and 12.00 mg/kg, respectively.…”
Section: Pharmacological Activities Of Acmentioning
confidence: 99%
“…With the exploration of traditional Chinese medicine (TCM), increasing evidence suggests that Chinese herbs have beneficial therapeutic effects on cancer patients. [ 7 ] Therefore, Chinese medicine treatments as complementary or alternative therapies have been widely accepted. [ 8 ] Mori Cortex is derived from the white inner bark of young mulberry roots, and possesses antiinflammatory, antioxidative stress, and immune-boosting properties.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a plethora of evidence has confirmed that gut microbiota dysbiosis is closely related to the occurrence and development of RA and OA and can further lead to synovitis and tenosynovitis, which is called the gut–joint axis ( Xiang et al, 2022 ; Xu et al, 2022 ). Based on the research of Liang et al, fecal comparative analysis of RA patients and healthy people indicated that the contents of Flavobacterium , Eisenbergia , Escherichia coli , and Klebsiella in the feces of RA patients were higher, while the contents of Enterococcus , Pseudomonas , and Fusobacterium in the feces of healthy individuals were higher ( Liang et al, 2023 ). According to some studies, fecal samples from RA patients were analyzed and showed an increase in Wallemia and Candida species abundance, while Trichosporon , Scedosporium , and Pholiota species abundance decreased, which further indicated that the difference in the fungal microbiome might contribute to the inflammatory reaction in RA patients ( Dagar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%